Preparation method for regulating and controlling morphology of zinc oxide nanorod

By adjusting the hydrothermal parameters to control the crystal growth of zinc oxide nanomaterials, the problem of difficulty in controlling the crystal surface exposure ratio in the prior art is solved, and the preparation of ZnO nanomaterials with different proportions is realized, which improves its performance in various application fields.

CN119551708APending Publication Date: 2025-03-04NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411924998.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the crystal surface exposure ratio of zinc oxide nanomaterials, affecting its application performance in the fields of catalysis, optoelectronic devices and sensors.

Method used

By adjusting hydrothermal parameters, including reaction temperature, time and molar ratio of ethylenediamine added, the crystal growth process of ZnO nanomaterials is controlled, thereby regulating the selective exposure of different crystal surfaces.

Benefits of technology

The preparation of ZnO nanomaterials with different crystal surface exposure ratios has been achieved, providing a broader application prospect, especially in the fields of catalysis, optoelectronic devices and sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551708A_ABST
    Figure CN119551708A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method for regulating and controlling the morphology of a zinc oxide nanorod, and belongs to the technical field of inorganic nanomaterials, Zn (Ac) 22H2O and sodium hydroxide are dissolved in 80-100 mL of ethanol solvent respectively according to the molar ratio of Zn (Ac) 22H2O to sodium hydroxide being 1: (2-30), and an ethanol solution of acetate and an ethanol solution of sodium hydroxide are obtained; slowly dropwise adding the ethanol solution of sodium hydroxide into the ethanol solution of acetate in a magnetic stirring state; adding an ethylenediamine reagent into the obtained solution, and continuing magnetic stirring; putting the mixture into a reaction kettle, and heating the reaction kettle at 120-200 DEG C to react for 0.25-3 hours, so as to obtain a reaction product; washing with deionized water and ethanol, and drying to obtain a ZnO nanorod; according to the method disclosed by the invention, ZnO nano materials with different crystal face exposure proportions can be prepared, and more possibilities are provided for application of the ZnO nano materials in the fields of catalysis, photoelectric devices, sensors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method for regulating the morphology of zinc oxide nanorods, and belongs to the technical field of inorganic nanomaterials. Background Art

[0002] Oxide nanomaterials are widely used in industry, commerce and personal products due to their unique structure and properties. Among them, zinc oxide, as an important semiconductor material, has a band gap of 3.4eV and an exciton binding energy of 60meV. It has special properties in thermoelectricity, piezoelectricity and biocompatibility. It has broad application prospects in optical devices, solar cells, electronic-related devices and industrial catalysis, and has therefore attracted much attention from researchers.

[0003] The application performance of ZnO nanomaterials is closely related to their exposed crystal faces. For example, in the field of catalysis, the non-polar crystal faces of ZnO have strong adsorption and activation capabilities for water molecules. Water molecules have two stable thermodynamic adsorption structures on the surface, namely (2×1) semi-dissociated adsorption structure and (1×1) monolayer molecular adsorption form; while the polar crystal faces of ZnO have a large number of defect sites on the surface due to electrostatic instability, showing strong photocatalytic activity. Therefore, it is extremely important to control the preparation of ZnO nanomaterials with different exposed crystal face ratios. Summary of the invention

[0004] In view of the technical problems existing in the above-mentioned prior art, the present invention provides a preparation method for regulating the morphology of zinc oxide nanorods. By adjusting the hydrothermal parameters, ZnO nanomaterials with different exposed crystal face ratios can be prepared.

[0005] The object of the present invention is achieved through the following technical scheme: a preparation method for regulating the morphology of zinc oxide nanorods, the method comprising the following steps:

[0006] Step S1, dissolving Zn(Ac)2·2H2O and sodium hydroxide in 80-100 mL of ethanol solvent respectively according to a molar ratio of Zn(Ac)2·2H2O to sodium hydroxide of 1:2-30 to obtain an ethanol solution of zinc acetate and an ethanol solution of sodium hydroxide;

[0007] Step S2, slowly adding the ethanol solution of sodium hydroxide to the ethanol solution of zinc acetate under magnetic stirring;

[0008] Step S3, adding ethylenediamine reagent to the solution obtained in step S2, and continuing magnetic stirring for 0.5-1.0h;

[0009] Step S4, placing the solution obtained in step S3 in a reaction kettle, heating the reaction at a temperature of 120-200° C. for 0.25-3 h to obtain a reaction product;

[0010] Step S5, washing the reaction product obtained in step S4 with deionized water and ethanol, and then drying to obtain ZnO nanorods.

[0011] Preferably, the amount of ethanol solvent used in step S1 is 80 mL.

[0012] Preferably, in step S3, the ethylenediamine reagent is obtained by adding 0.19-0.3 g of ethylenediamine to 3.0-5.0 ml of deionized water.

[0013] Preferably, the magnetic stirring time in step S3 is 0.5 h.

[0014] Preferably, in step S5, the drying temperature is 60-90° C. and the drying time is 8-10 h.

[0015] The invention has the following beneficial effects: the method of the invention can prepare ZnO nanomaterials with different crystal face exposure ratios, the method of the invention can effectively prepare ZnO nanomaterials with different crystal face exposure ratios, and the crystal growth process of the ZnO nanomaterial can be controlled by adding ethylenediamine during the reaction of Zn(Ac)2·2H2O and sodium hydroxide and adjusting the molar ratio, reaction temperature and time, thereby achieving selective exposure of different crystal faces, and providing more possibilities for its application in the fields of catalysis, optoelectronic devices and sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 XRD spectra of ZnO nanorods prepared in Examples 1-4;

[0017] Figure 2 XRD spectra of ZnO nanorods prepared in Examples 5-7;

[0018] Figure 3 XRD spectra of ZnO nanorods prepared in Examples 8-11;

[0019] Figure 4 TEM images of ZnO nanorods prepared in Examples 1-4 (Zn 2+ / OH - Molar ratio, a: 1:2, b: 1:10, c: 1:20, d: 1:30);

[0020] Figure 5 TEM images of ZnO nanorods prepared in Examples 5-7 (hydrothermal temperature, a: 120°C, b: 160°C, c: 200°C);

[0021] Figure 6 TEM images of ZnO nanorods prepared in Examples 8-11 (hydrothermal time, a: 0.25 h, b: 0.5 h, c: 1.0 h, d: 3.0 h);

[0022] Figure 7 XRD and TEM images of the products obtained in Examples 14 and 15 (D represents the ZnO nanorods prepared in Example 12, and E represents the ZnO nanorods prepared in Example 13);

[0023] Figure 8 The product obtained in Examples 14 and 15 17 O NMR spectra (D represents the ZnO nanorods prepared in Example 12, and E represents the ZnO nanorods prepared in Example 13). DETAILED DESCRIPTION

[0024] The following examples also describe certain specific aspects and embodiments, which are provided for illustrative purposes only and should not be construed as limiting the scope of the invention in any way.

[0025] XRD testing conditions: The XRD test in this patent uses the X'Pro diffractometer developed by Philips; specific conditions and parameters (Cu Kα ray (λ = 1.541 ); operating current: 40 mA; operating voltage: 40 kV; temperature: room temperature). The sample TEM was examined using a JEOL JEM-2010 high-resolution transmission electron microscope. 17 O NMR characterization was performed using a Bruker Avance III spectrometer with a magnetic field strength of 9.4 T.

[0026] Example 1

[0027] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 3.2 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0028] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0029] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0030] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 1 h to obtain a reaction product;

[0031] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0032] Example 2

[0033] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 16 mmol NaOH in 85 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0034] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0035] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0036] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 1 h to obtain a reaction product;

[0037] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0038] Example 3

[0039] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 32 mmol NaOH in 90 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0040] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0041] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0042] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 1 h to obtain a reaction product;

[0043] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0044] Example 4

[0045] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 48 mmol NaOH in 100 mL ethanol solvent respectively to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0046] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0047] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0048] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 1 h to obtain a reaction product;

[0049] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0050] Example 5

[0051] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 3.2 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0052] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0053] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0054] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 120° C. for 1 h to obtain a reaction product;

[0055] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0056] Example 6

[0057] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 3.2 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0058] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0059] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0060] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 1 h to obtain a reaction product;

[0061] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0062] Example 7

[0063] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 3.2 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0064] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0065] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0066] 4) placing the solution obtained in step 3) in a reaction kettle, heating the reaction kettle at 200° C. for 1 h to obtain a reaction product;

[0067] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0068] Example 8

[0069] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 3.2 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0070] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0071] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0072] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 0.25 h to obtain a reaction product;

[0073] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0074] Example 9

[0075] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 3.2 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0076] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0077] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0078] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 0.5 h to obtain a reaction product;

[0079] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0080] Example 10

[0081] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 3.2 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0082] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0083] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0084] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 1 h to obtain a reaction product;

[0085] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0086] Embodiment 11

[0087] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 3.2 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0088] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0089] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0090] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 3 h to obtain a reaction product;

[0091] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods.

[0092] Example 12

[0093] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 32 mmol NaOH in 90 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0094] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0095] 3) Add the solution obtained in step 2) to an aqueous solution containing 0.3 g of ethylenediamine in 5 mL of deionized water and continue magnetic stirring for 1 h;

[0096] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 1 h to obtain a reaction product;

[0097] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 60° C. for 10 h to obtain ZnO nanorods.

[0098] Example 13

[0099] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 48 mmol NaOH in 100 mL ethanol solvent respectively to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0100] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0101] 3) Add the solution obtained in step 2) to an aqueous solution containing 0.3 g of ethylenediamine in 5 mL of deionized water, and continue magnetic stirring for 0.5 h;

[0102] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 160° C. for 1 h to obtain a reaction product;

[0103] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 90° C. for 9 h to obtain ZnO nanorods.

[0104] Embodiment 14

[0105] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 48 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0106] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0107] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0108] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 120° C. for 3 h to obtain a reaction product;

[0109] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods, which were recorded as sample D.

[0110] Embodiment 15

[0111] 1) Dissolve 1.6 mmol Zn(Ac)2·2H2O and 3.2 mmol NaOH in 80 mL ethanol solvent to obtain an ethanol solution of Zn(Ac)2·2H2O and an ethanol solution of NaOH;

[0112] 2) Under magnetic stirring, slowly add the ethanol solution of NaOH to the ethanol solution of Zn(Ac)2·2H2O;

[0113] 3) Add the solution obtained in step 2) to 3 mL of an aqueous solution containing 0.19 g of ethylenediamine, and continue magnetic stirring for 0.5 h;

[0114] 4) placing the solution obtained in step 3) in a reaction kettle, and heating the reaction kettle at 200° C. for 0.25 h to obtain a reaction product;

[0115] 5) The reaction product obtained in step 4) was washed with deionized water and ethanol, and then dried at 80° C. for 8 h to obtain ZnO nanorods, which were recorded as sample E.

[0116] A series of tests and analyses were performed on the ZnO nanorod samples obtained in Examples 1-13. The results are as follows: Figure 1-8 The analysis results are as follows:

[0117] 1. By Figure 1-3 Analysis shows that the samples prepared by the method of the present invention are all typical wurtzite ZnO nanomaterials. According to the change in the relative intensity of the diffraction peak signal, it is shown that the method of the present invention can prepare ZnO nanomaterials with different crystal plane exposure ratios.

[0118] 2. By Figure 4 Analysis shows that the initial higher NaOH concentration in the present invention can obtain ZnO nanomaterials with high crystallinity and large aspect ratio.

[0119] 3. Pass Figure 5 It can be seen from the analysis that the higher hydrothermal temperature in the present invention leads to a relatively smaller aspect ratio of the ZnO nanorods.

[0120] 4. Pass Figure 6 Analysis shows that extending the hydrothermal reaction time of the raw materials in the present invention can improve the crystallinity of ZnO and obtain ZnO nanomaterials with a larger aspect ratio.

[0121] 5. Pass Figure 7 It can be seen from the analysis that, according to the preferred synthesis parameters, the method of the present invention can control the preparation of ZnO nanomaterials with different crystal surface exposure ratios.

[0122] 6. Pass Figure 8 Analysis shows that the ZnO prepared by the method of the present invention with different crystal surface exposure ratios corresponds to different 17 The O NMR signal intensity and relative proportion indicate that they correspond to different material surface microenvironments, such as surface coordination mode, surface OH and surface defect structure, etc. Therefore, ZnO nanomaterials with different morphologies can be prepared by the method of the present invention according to the needs in the field of environmental catalysis or energy catalysis.

[0123] The above description is only a preferred embodiment of the present invention, but is not intended to limit the present invention. Those skilled in the art may make possible changes and modifications to the present invention using the technical contents disclosed above without departing from the scope of the technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing zinc oxide nanorods by regulating their morphology, characterized in that: The method comprises the following steps: Step S1, dissolving Zn(Ac)2·2H2O and sodium hydroxide in 80-100 mL of ethanol solvent respectively according to a molar ratio of Zn(Ac)2·2H2O to sodium hydroxide of 1:2-30 to obtain an ethanol solution of zinc acetate and an ethanol solution of sodium hydroxide; Step S2, slowly adding the ethanol solution of sodium hydroxide to the ethanol solution of zinc acetate under magnetic stirring; Step S3, adding ethylenediamine reagent to the solution obtained in step S2, and continuing magnetic stirring for 0.5-1.0h; Step S4, placing the solution obtained in step S3 in a reaction kettle, heating the reaction at a temperature of 120-200° C. for 0.25-3 h to obtain a reaction product; Step S5, washing the reaction product obtained in step S4 with deionized water and ethanol, and then drying to obtain ZnO nanorods.

2. The method for preparing zinc oxide nanorods according to claim 1, characterized in that: The amount of ethanol solvent used in step S1 is 80 mL.

3. The method for preparing zinc oxide nanorods according to claim 1, characterized in that: In step S3, the ethylenediamine reagent is obtained by adding 0.19-0.3 g of ethylenediamine to 3.0-5.0 ml of deionized water.

4. The method for preparing zinc oxide nanorods for controlling the morphology according to claim 1, characterized in that: The magnetic stirring time in step S3 is 0.5 h.

5. The preparation method for regulating the morphology of zinc oxide nanorods according to claim 1, characterized in that: In step S5, the drying temperature is 60-90° C. and the drying time is 8-10 hours.